Post-tensioning the inverted-t bridge system for improved durability and increased span-to-depth ratio - Nayal, Rim (Kansas State University, 2006)
Possibly the most pressing need in highway construction today is the repair or replacement of existing bridges. Due to increased needs and growing traffic, in addition to aging and extensive use, more than 2000 bridges in Kansas alone need to be replaced during the next decade. The majority of these bridges has spans of 100 ft or less, and has relatively shallow profiles. It is becoming increasingly important to implement a standard method for replacement in which the process is expedited and accomplished in cost-effective manner. Requirements for design and construction of concrete bridges have drastically changed during recent years. A main change in design is live-load requirements. Nebraska inverted-T bridge system has gained increasing popularity for its lower weight compared to I-girder bridges. However, there are some limiting issues when using IT system in replacing existing CIP bridges. Implementation of a post-tensioned IT system, which is the focus of this research, is believed to be one excellent solution for the IT deficiencies. Post-tensioning is added by placing a draped, post-tensioning duct in the stems of the IT members. Post-tensioning will lead to a higher span-to-depth ratio than IT system, and will reduce the potential transverse cracks in the (CIP) deck. Finally, the undesired cambers of pretensioned beams will be reduced, because fewer initial prestressing will be needed. This study was intended to explore the behavior of the PT-IT system, identify major parameters that control and limit the design of this system, and investigate different construction scenarios. This was achieved by conducting an extensive parametric study. For that purpose, PT-IT analysis program was developed and written using C++ programming language. The program was used to analyze various post-tensioning procedures for the post-tensioned inverted-T system. A Visual Basic friendly interface was provided to simplify the data input process. The findings of this research included recommendation of construction scenario for PT-IT system, as well as examining different methods for estimating time-dependent restraining moments. Effect of different concrete strengths on the behavior of PT-IT system was also determined. Most importantly, the effect of timing on different construction stages was also evaluated and determined.
Keywords: Post-Tensioning; Precast; Prestressed; Inverted-T; Bridge; system; Engineering, Civil (0543)